2017
DOI: 10.1111/jcal.12181
|View full text |Cite
|
Sign up to set email alerts
|

Early reading intervention by means of a multicomponent reading game

Abstract: This study examined the effects of an intervention with a multicomponent reading game on the development of reading skills in 60 Dutch primary school children with special educational needs. The game contains evidence‐based reading exercises and is based on principles of applied gaming. Using a multiple baseline approach, we tested children's word, pseudoword and text reading fluency, as well as their reading motivation, at three test occasions. The results indicated that the short intervention (9 × 15 min) en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 84 publications
3
22
0
Order By: Relevance
“…The results support our first hypothesis by showing that a 6-week intervention with GL carried out by teachers and parents (here with a mean exposure time of 5 h) seems to improve the children's word reading skill. The results are in line with the earlier studies that have found evidence of positive effects of short game-based interventions on the reading skills of children (Heikkilä et al 2013;Hintikka et al 2008;Lovio et al 2012;Van de Ven et al 2017;Van Gorp et al 2016). The current study extends these previous studies by showing that serious games that train reading skills can be effective also with children who have moderate to severe reading disabilities, which are often laborious to remediate using conventional instruction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results support our first hypothesis by showing that a 6-week intervention with GL carried out by teachers and parents (here with a mean exposure time of 5 h) seems to improve the children's word reading skill. The results are in line with the earlier studies that have found evidence of positive effects of short game-based interventions on the reading skills of children (Heikkilä et al 2013;Hintikka et al 2008;Lovio et al 2012;Van de Ven et al 2017;Van Gorp et al 2016). The current study extends these previous studies by showing that serious games that train reading skills can be effective also with children who have moderate to severe reading disabilities, which are often laborious to remediate using conventional instruction.…”
Section: Discussionsupporting
confidence: 91%
“…The present study extends the previous studies conducted with GL and other serious games by focusing on second graders who, first, have moderate to severe disabilities in reading accuracy and/ or fluency (i.e., belonging to the lowest 14th percentile of their grade level; see Galuschka et al 2014) and, second, have not been able catch up with the other students with the help of the standard support provided by school (remedial reading lessons and part-time special education) in first grade. Previous studies (Heikkilä et al 2013;Hintikka et al 2008;Lovio et al 2012;Saine et al 2010;Van de Ven et al 2017;Van Gorp et al 2016) have shown that games, like reading interventions in general (Galuschka et al 2014), can have a positive effect on the reading skills of children who have mild reading difficulties. However, children with severe reading disabilities have been underexamined in previous studies addressing the effects of game-based learning.…”
Section: Research Questionsmentioning
confidence: 99%
“…programs provides a holistic approach for improving fluency, considering its complex and multifaceted nature. The use of technology to improve the automaticity and speed of reading can be really useful, especially because, automaticity and speed in reading needs mastery in multiple levels of decoding, but, in typical school conditions there is not enough practice for struggling readers to reach mastery levels in decoding (Vellutino, Fletcher, Snowling, & Scanlon, 2004).…”
Section: Interventionsmentioning
confidence: 99%
“…It can be divided into lower order skills—phonological awareness, grapheme‐to‐phoneme conversion, lexical recall, reading fluency—and higher order (so called “complex”) skills (reading strategies, inference, word‐to‐text integration, and reading comprehension). Our current study has addressed the former (early reading development; Van de Ven et al, ), although it is entirely possible that more complex skills also undergo some long‐term alterations. Literacy research has identified various cognitive skills that contribute to early reading development.…”
Section: Enhancing Reading Skillsmentioning
confidence: 99%
“…Reading games have received scant attention in the literature. Earlier studies have indicated appropriate training methods for enhancing early literacy development (e.g., Lundberg, Frost, & Petersen, ; Van de Ven, De Leeuw, Van Weerdenburg, & Steenbeek‐Planting, ). To the best of our knowledge, this is one of the first studies attempting to develop an adaptive data‐driven language‐learning game (DLLgame) to improve early reading ability of children.…”
Section: Introductionmentioning
confidence: 99%